Numeracy literacy of junior high school students in implementing the Merdeka mathematics learning curriculum - Nuryami Nuryami (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Numeracy literacy skills play a crucial role in the Independent Learning Curriculum. Currently, students' literacy skills are geared towards more independent learning. With these skills, students can solve problems accurately and develop critical thinking towards their challenges. This study aims to evaluate students' abilities in numeracy literacy in the era of more independent learning. This study focuses on eighth-grade students at SMP Muhammadiyah 1 Probolinggo, consisting of 28 students who have followed the Independent Curriculum. This study uses a qualitative descriptive method, collecting data through written tests with five questions encompassing various aspects of numeracy literacy skills. Indicators for numeracy literacy skills include (1) Using numbers and mathematical symbols to solve everyday problems; (2) Analyzing information in various forms (graphs, tables, etc.; and (3) Interpreting analysis results to predict, formulate, and make decisions. Data were analyzed by calculating the average percentage for each indicator of numeracy literacy skills. The analysis results show that the numeracy literacy skills of junior high school students in the era of independent learning are still at a low level.